If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + -1x + 3 = 15 Reorder the terms: 5 + 3 + 2x + -1x = 15 Combine like terms: 5 + 3 = 8 8 + 2x + -1x = 15 Combine like terms: 2x + -1x = 1x 8 + 1x = 15 Solving 8 + 1x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = 15 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 15 + -8 1x = 15 + -8 Combine like terms: 15 + -8 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| f(-3)=4x^2+8x-3 | | 2x+7x-5=30 | | y=4x^2+8-3 | | 16x-8y=24 | | (mx+1)(x+m)=(mx+1)(2x+m) | | 6(4y+5)=3(y+8)+3 | | 7x-4=2x+1 | | 12=2x+6 | | 4x+3x-5=10 | | 6m^2+11m+4= | | 20b^2-16b=0 | | 9k^3+45k^2+2k+10= | | 10-8x=34-29x | | x^3-11x^2-x+11=0 | | 6x^8-36x^6= | | 6x+22=13x-62 | | 3(2x-1)+2=2(x+3)-1 | | 5dx+6=2x-3 | | (X-3)+5=4(2x-5) | | 4-2(3-x)=7-x | | 7x-3=8+2x | | 5x-2=8x+7 | | b^2+b-9=0 | | -3x-8=4x-15 | | 1=4x+13 | | 6x-95=55 | | -z=-38 | | 8(3-x)=16 | | -9=11z | | p=3g+3w | | 8=k+20 | | -x+18=83 |